Fifty years of progress in sheep production - Menzies, C. (Kansas Agricultural Experiment Station, 2011)
Research has provided the basis for improving production of quantity and quality of lamb and wool. Knowledge obtained concerning improved breeding, feeding, management and disease control practices has been used to increase profits through more efficient production of quality lamb and wool.
Keywords: Sheep; Wool quality; Nutrition; Breeding